2019
DOI: 10.1080/09638288.2019.1687763
|View full text |Cite
|
Sign up to set email alerts
|

Vibroacoustic treatment to improve functioning and ability to work: a multidisciplinary approach to chronic pain rehabilitation

Abstract: Vibroacoustic treatment to improve functioning and ability to work : a multidisciplinary approach to chronic pain rehabilitation. Disability and Rehabilitation, Early online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 53 publications
1
21
2
Order By: Relevance
“…Some studies have shown the effect of VAT in patients with different types of health problems. They focused on, for instance, heart rate variability [10,11], galvanic skin response [10], and blood pressure and pulse rate [12,13]. These research studies, like the present one, made use of questionnaires, self-assessment scales and interviews [14,15].…”
Section: Introductionmentioning
confidence: 97%
“…Some studies have shown the effect of VAT in patients with different types of health problems. They focused on, for instance, heart rate variability [10,11], galvanic skin response [10], and blood pressure and pulse rate [12,13]. These research studies, like the present one, made use of questionnaires, self-assessment scales and interviews [14,15].…”
Section: Introductionmentioning
confidence: 97%
“…Eleven studies were focused on chronic pain,2 4 16 17 26–32 two on acute pain,15 33 one study on experimentally induced pain34 (from this point onwards referred to only as experimental pain), one study included patients with acute and chronic pain35 and one study did not specify the type of pain (probably both acute and chronic pain patients were included) 5. Chronic pain included different types of presumed musculoskeletal pain (mostly fibromyalgia), psychosomatic and neuropathic conditions,2 4 16 26–32 35 and, least prevalent, Ehlers-Danlos Syndrome Hypermobility Type 17. The acute pain15 33 studies included postoperative pain after gynaecological surgeries, after a total knee replacement and after an ankle sprain 35.…”
Section: Resultsmentioning
confidence: 99%
“…The one study on experimental pain was published in 2012 34. Four of the studies on chronic pain were from Canada,16 17 30 31 four from Finland,2 4 26 27 three from the USA28 29 35 and one from Estonia 32. The studies on acute pain were from the USA,15 33 35 and the study on experimental pain was from Canada 34.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism by which the body reacts to sound frequencies and vibration is referred to as resonance (45). But this applies not only to the body but also to the resonant oscillations within the brain, defined as the steady‐state response, which is evoked from rhythmic stimulation (46).…”
Section: Discussionmentioning
confidence: 99%